P2Y6 receptor activation is necessary to induce phagoptosis of neurons by b. abortus-activated microglia - Fiorillo Evequoz, Ariadna Maria (2022)
B. abortus-activated microglia kill neurons through primary phagocytosis or phagoptosis. Phagocytosis is a finely regulated process that involves the interaction of different receptors and their ligands. It has been shown that the purinergic pathway is involved in the modulation of different functions of phagocytes. The objective of this work was to investigate whether this signaling pathway is involved in the phagoptosis of neurons mediated by B. abortus-activated microglia. Primary cultures of neurons and microglia from Balb/c mice were infected. Neuron survival was assessed at 48 h by fluorescence microscopy. Co-cultures were treated with apyrase (an enzyme that degrades di and tri nucleotides), Reactive Blue 2 (RB2) (a P2X/P2Y purinergic receptor inhibitor), BBG (a P2X7 specific inhibitor) and MRS2578 (a P2Y6 specific inhibitor). Treatment of B. abortus-infected co-cultures with apyrase inhibited neuronal death, when compared to untreated cultures (p<0.05). Treatment of B. abortus-infected co-cultures with RB2 also prevented neuronal death (p>0.05). By using the specific inhibitors of P2X7 and P2Y6, we were able to demonstrate that the P2Y6, but not P2X7 purinergic receptor, is involved in the modulation of phagoptosis (p>0.05). In all cases microglia activation was not affected since TNF-α secretion was not significant different between treatments (p>0.05). These results demonstrate that the P2Y6 purinergic receptor and the nucleotides that activate it would be necessary for neuronal death mediated by microglia activated by B. abortus, describing new molecular mechanisms involved in the pathogenesis of neurobrucellosis.